2008
DOI: 10.1111/j.1529-8817.2008.00502.x
|View full text |Cite
|
Sign up to set email alerts
|

CHANGES IN THE MORPHOLOGY AND POLYSACCHARIDE CONTENT OF MICROCYSTIS AERUGINOSA (CYANOBACTERIA) DURING FLAGELLATE GRAZING1

Abstract: To investigate the changes in the morphology and polysaccharide content of Microcystis aeruginosa (Kütz.) Kütz. during flagellate grazing, cultures of M. aeruginosa were exposed to grazing Ochromonas sp. for a period of 9 d under controlled laboratory conditions. M. aeruginosa responded actively to flagellate grazing and formed colonies, most of which were made up of several or dozens of cells, suggesting that flagellate grazing may be one of the biotic factors responsible for colony formation in M. aeruginosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 201 publications
(119 citation statements)
references
References 27 publications
4
113
2
Order By: Relevance
“…In our study, the content of sEPS and bEPS in induced colonial M. aeruginosa were significantly higher than in unicellular algae. This result is consistent with previous ones, when M. aeruginosa was directly exposed to flagellates (Yang et al, 2008). The infochemicals released from the flagellates may be a main stimulator for the increased production of EPS in M. aeruginosa, which sticks algae cells together to form colonies.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, the content of sEPS and bEPS in induced colonial M. aeruginosa were significantly higher than in unicellular algae. This result is consistent with previous ones, when M. aeruginosa was directly exposed to flagellates (Yang et al, 2008). The infochemicals released from the flagellates may be a main stimulator for the increased production of EPS in M. aeruginosa, which sticks algae cells together to form colonies.…”
Section: Discussionsupporting
confidence: 82%
“…Several laboratory experiments have reported that the formation of colonies or aggregates might be a response by Microcystis to various environmental stresses. Burkert et al (2001) and Yang et al (2008) showed induction of colonies in axenic M. aeruginosa in the presence of the predator Ochromonas. Sedmak & Eleršek (2005) reported that unicellular M. aeruginosa strains aggregated in the presence of commercial microcystins.…”
Section: Cell Aggregationmentioning
confidence: 99%
“…Previous laboratory studies (Shen & Song, 2007;Wu et al, 2007) indicated that unicellular and colonial Microcystis display different physiological characteristics, especially in terms of their responses to environmental stress. Formation of colonies or aggregates could be induced by flagellate grazing (Burkert et al, 2001;Yang et al, 2008) and by extracellular microcystins (Sedmak & Eleršek, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Bloom-forming cyanobacteria generally exist as massive or filamentous colonies. Among the many features associated with large colonial forms of cyanobacteria include quick vertical migration (Kromkamp and Walsby, 1990), effective uptake of phosphorus (Shen and Song, 2007), protection from ultraviolet radiation (Sommaruga et al, 2009) and invulnerability to grazers (Ghadouani et al, 2003;Yang et al, 2008). These features are closely related to the ecological advantages of bloom-forming cyanobacteria over unicellular species in water ecosystems.…”
Section: Introductionmentioning
confidence: 99%